Synthesis and polymerase chain reaction amplification of DNA strands containing an unnatural triazole linkage. - El-Sagheer, A; Brown, T (2009)
DNA strands containing an unnatural T-triazole-T linkage have been synthesized by click DNA ligation between oligonucleotides with 3'-AZT and 5'-propargylamido dT and amplified efficiently by polymerase chain reaction (PCR) using several different polymerases. DNA sequencing of PCR amplicons and clones in two different sequence contexts revealed the presence of a single thymidine at the ligation site. The remarkable ability of thermostable polymerases to reproducibly copy DNA templates containing such an unnatural backbone opens up intriguing possibilities in gene synthesis, genetic analysis, biology, and nanotechnology.